Clinical and prognostic relevance of sST2 in adults with dengue-associated cardiac impairment and severe dengue. - Andrew Teo; Po Ying Chia; Gaurav Kumar Ramireddi; Sebastian Kah Ming Khoo; Tsin Wen Yeo (Public Library of Science (PLoS), 2022)
Background Dengue can be complicated by severe outcomes including cardiac impairment, and the lack of reliable prognostic biomarkers poses a challenge in managing febrile dengue patients. Here, we investigated the functionality of soluble suppressor of tumorigenicity (sST2) as a predictive marker of severe dengue and its association in dengue-associated cardiac impairment. Methods Plasma samples, aged >16 years, collected from 36 dengue fever, 43 dengue with warning signs, 11 severe dengue (collected at febrile, critical and recovery phases) and 30 controls were assayed for plasma levels of sST2, troponin T and N-terminal (NT)-pro hormone brain natriuretic peptide (NT-proBNP) by ELISA. Cardiac parameters: stroke index (SI), cardiac index (CI) and Granov-Goor Index (GGI) were measured with a bioimpedance device during the different phases for dengue subjects and once for the controls. Principal findings In the febrile, critical and early recovery phases, sST2 levels were significantly elevated in dengue participants and sST2 levels increased with increasing disease severity (P < 0.01 for all). sST2 concentrations were negatively correlated with SI (r = -0.48; P < 0.001, r = -0.55; P < 0.001), CI (r = -0.26; P = 0.02, r = -0.6: P < 0.001) and GGI (r = -0.44; P < 0.001, r = -0.57; P < 0.001) in the critical and early recovery phases. In contrast, sST2 levels in the febrile and critical phases, were positive correlated to troponin T (r = 0.44, P < 0.001; r = 0.22, P = 0.03, respectively) and NT-proBNP (r = 0.21, P = 0.03; r = 0.35, P < 0.001). ROC analysis demonstrated sST2 as a good biomarker of severe dengue in the critical phase, AUROC 0.79, P < 0.001. Conclusion/significance sST2 levels were elevated in patients with dengue especially in cases of severe dengue. Furthermore, increased sST2 levels were associated with cardiac indicators suggesting lower cardiac performance. While further research is needed to demonstrate its clinical utility, sST2 may be a useful prognostic biomarker of severe dengue.